2021
DOI: 10.1093/alcalc/agaa144
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analyses for Missing Data in Meta-Analyses and Meta-Regression: A Tutorial

Abstract: Objectives In this tutorial, we examine methods for exploring missingness in a dataset in ways that can help to identify the sources and extent of missingness, as well as clarify gaps in evidence. Methods Using raw data from a meta-analysis of substance abuse interventions, we demonstrate the use of exploratory missingness analysis (EMA) including techniques for numerical summaries and visual displays of missing data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Recent empirical work on examining missingness in meta-analytic datasets found that effect sizes can be strongly correlated with missingness, though this is not always the case. 48…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent empirical work on examining missingness in meta-analytic datasets found that effect sizes can be strongly correlated with missingness, though this is not always the case. 48…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is not immediately clear how commonly the conditions required for unbiased complete‐ and shifting‐case estimators arise. Recent empirical work on examining missingness in meta‐analytic datasets found that effect sizes can be strongly correlated with missingness, though this is not always the case 48 . Further, the issues of multicollinearity and confounding in meta‐regression, including those discussed by Lipsey, 25 would suggest that omitting variables in an SCA are likely to induce bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applied meta‐analysts are likely to encounter missing data in the moderators because some primary studies may not provide all the information needed to code predictor variables 52 . Schauer and colleagues 53 are currently developing and testing multiple imputation methods for meta‐analyses with dependent data. Once these techniques are more established with typical meta‐analytic methods, future studies should extend them to integrate with cluster wild bootstrapping.…”
Section: Discussionmentioning
confidence: 99%